Bridging the goal intention–action gap in rehabilitation: a study of if-then implementation intentions in neurorehabilitation. (June 2015) - Kersten, Paula; McPherson, Kathryn M.; Kayes, Nicola M.; Theadom, Alice; McCambridge, Alana
Abstract Purpose: To test the feasibility and acceptability of an implementation intention strategy (if-then plans) increasingly used in health psychology to bridge the goal intention–action gap in rehabilitation with people with neurological conditions who are experiencing difficulties with mobility. Methods: Twenty people with multiple sclerosis (MS) and stroke, randomised to an experimental and control group, set up to three mobility related goals with a physiotherapist. The experimental group also formulated if-then plans for every goal. Data collection: Focus groups and interviews with participants and therapists; Patient Activation Measure (PAM), 10-m walk test, Rivermead Mobility Index, self-efficacy, subjective health status, quality of life. Results: Qualitative data highlighted one main theme: Rehabilitation in context, encapsulating the usefulness of the if-then strategy in thinking about the patient in the context of complexity, the usefulness of home-based rehabilitation, and the perceived need for a few more sessions. Changes in walking speed were in the expected direction for both groups; PAM scores improved over 3 months in both groups. Conclusion: If-then plans were feasible and acceptable in bridging the goal intention–action gap in rehabilitation with people with MS and stroke, who are experiencing difficulties with mobility. This approach can now be adapted and trialled further in a definitive study. Implications for Rehabilitation Goal planning in rehabilitation necessitates specific strategies that help people engage in goal-related tasks. If-then plans aim to support people to deal more effectively with self-regulatory problems that might undermine goal striving and have been found to be effective in health promotion and health behaviour change. This feasibility study with people with a stroke and multiple sclerosis has demonstrated that if-then plans are feasible and acceptable to patients and physiotherapists in supporting goal-directed behaviour.